Pengaruh Return On Equity, Rasio Operasi, Dan Cash Ratio Terhadap Tingkat Kesehatan Keuangan Yang Dimoderasi Oleh Penyertaan Modal dan Efektivitas Penagihan (Studi pada PDAM Bantul Tahun 2009-2019) - Arinto Hendro Budiantoro; Sri Hermuningsih; Gendro Wiyono (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
The finacial health of a company pertains its effort to mantain its survivability and industrial activities as well as measuring how far as a business entity can ensure its sound operation. The level of a company’s finacial health can be known by measuring its finacial performance. In this research financial health is studied with its correlation with Return On Equity, Operating Ratio, Cash Ratio, Equity Participation, and Colection Effectiveness. Return On Equity (ROA) measures the effectiveness of a company in maximizing its assets. Operating Ratio in this study relies on Net Profit Margin (NPM). This indicates how far the percentage of net income coming from each sale. Cash ratio is a measurement of minimum liquidity that a company must maintain. Equity Participation in this research refers to investment capital provided by the government either as equity or in the form of direct investment. Collection effectiveness describes the ratio between results from collection attempts relative to specified target.